Understanding Atrocities Remembering, Representing, and Teaching Genocide - Amarasingam, Amarnath 1982- (Arts in Action, 2017)
Front Cover -- Half title page -- Series page -- Full title page -- Copyright page -- Dedication -- Contents -- List of Figures -- Acknowledgements -- Abbreviations -- Introduction -- 1: Atrocity and Proto-Genocidein Sri Lanka -- 2: Finding Global Justice Locally at Sites of Atrocity: The Case for the Srebrenica-Potočari Memorial Center and Cemetery -- 3: Troubling History, Troubling Law: The Question of Indigenous Genocidein Canada -- 4: The Benefits and Challenges of Genocide Education: A Case Study of the Armenian Genocide -- 5: "We Charge Genocide": A Historical Petition All but Forgotten and Unknown -- 6: "A Tragedy to be Sure": Heteropatriarchy,Historical Amnesia, and Housing Crises in Northern Ontario -- 7: Remembering Them All: Including and Excluding Atrocity Crime Victims -- 8: Helping Children Understand Atrocities: Developing and Implementing an Undergraduate Course Titled Warand Genocide in Children's Literature -- 9: Thinking About Nazi Atrocities Without Thinking About Nazi Atrocities: Limited Thinking as Legacy in Schlink's The Reader -- 10: Atrocity, Banality, and Jouissance in Performance -- Contributors -- Index -- Back cover.